ANALYSIS OF THE IMPACT OF ACCOUNTABILITY AND TRANSPARENCY ON THE QUALITY OF FINANCIAL REPORTS WITH INTERNAL CONTROL SYSTEM AS A MODERATING VARIABLE - Raspati, Gun Gun Mugia; Simanjuntak, Binsar H (Multifinance, 2024)
The main objective of this research is to analyze the impact of accountability and transparency on the quality of ANRI financial reports and the internal control system as a moderating variable. The study employs a causal impact method, aided by descriptive data analysis and regression weight analysis using AMOS 18, with a research sample of 85 ANRI employees selected through probability sampling and random sampling strategies. The research results indicate that accountability at ANRI is categorized as fairly good, while transparency, the quality of financial reports, and the internal control system at ANRI are categorized as good. Furthermore, the study shows that accountability and transparency collectively have a significant influence on the quality of financial reports at ANRI. Transparency, in partial terms, has a positive and significant impact on the quality of financial reports, while accountability has a positive but not significant influence on the quality of financial reports at ANRI. The internal control system strengthens the relationship, significantly enhancing the impact of transparency on the quality of financial reports, but the internal control system does not significantly strengthen the impact of accountability on the quality of financial reports at ANRI.